Pharmacokinetic Evaluation of Niacin and Pterostilbene in Single and Multi-Doses in Healthy Subjects - Peer, Abdul Hannan; Abbas, Sudhair; Ullah, Irfan; Shakeel, Faisal; Ullah, Rahim; Khan, Muhammad Asif (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: The potential of natural antioxidants blends in metabolic syndromes and other ailments have been repeatedly investigated. Majority of studies are based on pharmacologic interactions and limited on their pharmacokinetic interactions. This study aimed to provide insight about pharmacokinetic interactions of niacin and pterostilbene upon concurrent administration and to quantify their blood concentrations in single and multiple doses. Methodology: A randomized, open label, crossover design was followed to study pharmacokinetic interaction between niacin (NA) and pterostilbene (PT) in single- and multi-dose combinations in healthy volunteers. Subjects were administered with single and multiple doses (250mg/dose each) in individual and combinations for one week. Blood samples were collected and analyzed on newly developed HPLC-UV method for simultaneous quantification employing hexa-decyltrimethylammonium-bromide as ion pairing. Results: Our method was found linear over applied concentration range (0.020-20µg mL-1) and sensitive (lower quantification limits were 50 and 22ng mL-1 for NA and PT). Pharmacokinetic profiling (Cmax, Tmax, AUC, MRT, and t1/2) of administered antioxidants showed no significant influence of analytes over one another in both single and multidose therapies. Comparing individual vs. combinations, statistically insignificant (p>0.05) variations were observed in plasma drug concentrations. Conclusion: Findings of this study revealed the biocompatibility of test drugs proven by pharmacokinetic data and therefore can be used safely at their recommended doses in combined formulations.